Cybersecurity capability maturity models review and application domain - Abdullahi Garba, Adamu; Musa Bade, Aliyu; Yahuza, Muktar; Nuhu, Ya’u (International Journal of Engineering and Technology, 2020)
Cybersecurity is a way of protecting organization critical assets, through the identification of cyber threats that can compromise the information stored, it involves the protection, identification, and responding to threats. The main aim of this article is to conduct an ample review of the published cybersecurity capability maturity models using a systematic review of published articles from 2014 to 2019. Features of Hal- vorsen and Conradiâ€™s taxonomy were adopted to explain the models identified. The results indicated adopting a model to a certain organization is not feasible. However, modification is required before implementation, as the cost of implementation is not available when conducting this research.Â Â